Hyphema due to blunt injury: A review of 118 patients - Ulagantheran, V.; Fauzi, M.S.A.; Reddy, S.C. (IJO Press, 2010)
AIM: To determine the causes, associated ocular findings and visual acuity on presentation, complications and visual outcome following treatment in patients of hyphema due to blunt injury METHODS: A retrospective study was performed in 118 patients with hyphema due to blunt injury admitted in University of Malaya Medical Centre, Kuala Lumpur, Malaysia. The gender, age, race, cause of blunt injury resulting in hyphema, eye involved, vision at admission, other associated ophthalmological findings, complications and visual outcome were noted from the case records of patients. The data were analyzed using SPSS programme. RESULTS: Males were more predominantly affected (93.2%). Two-thirds of patients (67.8%) were aged below 30 years. Sports related injury (38.1%) was the most common cause for hyphema. Hyphema disappeared within 5 days in 66.9% of patients. Iris injuries were very commonly associated in the form of mydriasis, sphincter tear and iridodialysis. Associated vitreous haemorrhage was noted in 11.9% of patients. During the hospital stay, secondary haemorrhage was observed in 3.4% of patients. The best corrected vision of 6/18 or better was noted in 85.4% of patients at the last follow-up. The follow-up of these subjects was very poor and thus the incidence of secondary glaucoma could not be established. Moderate blood staining of cornea occurred in 0.8% of patients. CONCLUSION: Sports related injury is the most common cause of hyphema in Malaysia. Good visual recovery, without serious complications, is possible with appropriate and in-time treatment in hyphema patients due to blunt injury.